Role of Adrenal Vein Sampling in Guiding Surgical Decision in Primary Aldosteronism - Younes, Nada; Larose, Stéphanie; Bourdeau, Isabelle; Therasse, Eric; Lacroix, André (Experimental and Clinical Endocrinology & Diabetes, 2023)
Adrenal vein sampling (AVS) is recommended for subtyping primary aldosteronism (PA) to identify lateralized or bilateral sources of aldosterone excess, allowing for better decision-making in regard to medical or surgical management on a case-by-case basis. To date, no consensus exists on protocols to be used during AVS, especially concerning sampling techniques, the timing of sampling, and whether or not to use adrenocorticotropic hormone (ACTH) stimulation. Interpretation criteria for selectivity, lateralization, and contralateral suppression vary from one expert center to another, with some favoring strict cut-offs to others being more permissive. Clinical and biochemical post-operative outcomes can also be influenced by AVS criteria utilized to indicate surgical therapy.In this review, we reanalyze studies on AVS highlighting the recent pathological findings of frequent micronodular hyperplasia adjacent to a dominant aldosteronoma (APA) overlapping with bilateral idiopathic hyperaldosteronism (IHA) etiologies, as opposed to the less frequent unilateral single aldosteronoma. The variable expression of melanocortin type 2 receptors in the nodules and hyperplasia may explain the frequent discordance in lateralization ratios between unstimulated and ACTH- stimulated samples. We conclude that aldosterone values collected during simultaneous bilateral sampling, both at baseline and post-ACTH stimulation, are required to adequately evaluate selectivity, lateralization, and contralateral suppression during AVS, to better identify all patients with PA that can benefit from a surgical indication. Recommended cut-offs for each ratio are also presented.
Keywords: adrenal vein sampling; primary aldosteronism; ACTH stimulation; adrenalectomy; contralateral basal suppression